PERAN DINAS LINGKUNGAN HIDUP DALAM MENINGKATKAN PARTISIPASI MASYARAKAT MELALUI PROGRAM PEMBERDAYAAN PENGELOLAAN SAMPAH DI KECAMATAN BANYUWANGI KABUPATEN BANYUWANGI - Andrian, Viki; Wilujeng, Sri; Pahlevi Hentika, Niko (JURNAL KATARSIS, 2025)
This analysis discusses the role of the Environmental Agency in increasing community participation through waste management empowerment programs in Banyuwangi District.The main issue lies in the low community participation in waste management at the source, which is caused by a lack of understanding and awareness among the community.The purpose of this research is to describe the role of the Environmental Agency as well as the supporting and inhibiting factors in the program.The methodology used is qualitative research with a descriptive approach, involving interviews and observations at the research site.The research results show that the Environmental Agency has taken various actions, such as providing information, consultations, and joint decision-making, but there are still obstacles in terms of budget and public awareness.The conclusion of this research emphasizes the need for increased socialization and guidance to enhance community participation in waste management, as well as the necessity for adequate budgetary support to sustain existing programs.